Computable majorants of the limit load in Hencky's plasticity problems. (1st January 2018) - Repin, Sergey; Sysala, Stanislav; Haslinger, Jaroslav
Abstract: We propose a new method for analyzing the limit (safe) load of elastoplastic media governed by the Hencky plasticity law and deduce fully computable bounds of this load. The main idea of the method is based on a combination of kinematic approach and new estimates of the distance to the set of divergence free fields. We show that two sided bounds of the limit load are sharp and the computational efficiency of the method is confirmed by numerical experiments.